Stem Cell Therapy- An Overview - Jagiri, Aishwarya Goud; Gotte, Priyanka; Singireddy, Swetha; Kadarla, Rohith Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Stem cells are defined as cells that have clonogenic and self-renewing capabilities and differentiate into multiple cell lineages. Stem cells are found in all of us, from the early stages of human development to the end of life. According to differentiation potential stem cells are divided into 5 types: totipotent, pluripotent, multipotent, oligopotent and unipotent. They are vital to the development, growth, maintenance, and repair of our brains, bones, muscles, nerves, blood, skin, and other organs. Stem cell therapy is emerging as a potentially revolution ary new way to treat disease and injury, with wide-ranging medical benefits. Stem cell research presents many ethical and scientific questions as well as future challenges. Stem cell therapy, a prologue to an era of medical discovery of cell-based therapies that will one day restore function to those whose lives are now challenged every day, is still at the beginning of the road. . Stem cells have great potential in tissue regeneration and repair but much still needs to be learned about their biology, manipulation and safety before their full therapeutic potential can be achieved.